Marketing strategy for a late follower in mass spectrometry equipment - Reyes, Julio Rodrigo J.; Cruz, Edison (Quezon City University of the Philippines Diliman, Technology Management Center, 2013)
Shimadzu Philippines Corporation (SPC) is a direct subsidiary of Shimadzu Corporation Japan tasked to handle the sales, marketing and after-sales-support of the Shimadzu product in the Philippines.
Shimadzu Corporation developed a liquid chromatograph triple quadrupole mass spectrometry (LCMS/MS) to compete with market leaders such as Waters and AB Sciex. However, the late-follower strategy of the main company brings challenges to marketing subsidiaries to win against competition. Shimadzu Japan and Shimadzu Asia Pacific (SAP) conducts training and educates subsidiaries of the marketing strategy and the product's target market based on their existing market. These may not apply to the local setting due to the difference in laws, competitive environment and client demands.
Majority of the marketing strategy proposed by the main company is applicable to the Philippines especially those that pertain to the product and price-leadership strategy. However, market segmentation based on the application of the LCMS/MS will not work since the market is very small. Thus, the market is segmented based on buying characteristics, source of funding, and ownership of the company. For the Philippines, it is best to segment the market as government and private companies. The presence of procurement laws in the government segment affects the company's strategy in marketing while private companies rely heavily on relationship marketing. Also the promotional mix is not dictated and left to the subsidiary to identify and implement.
SPC must take advantage of being a subsidiary against competitor going through distributors to deal their products. However, the lack of technical capabilities, synergy, and one direction of SPC must be addressed. The implementation of the CRM should be maximized to come up with valuable marketing information rather than just monitoring transactions.
The proposed marketing strategy suggests that the product must always be offered as a total solution including complementary products ensuring a 100 percent working instrument. SPC should continue with the price leadership strategy inherited from the main company as an aggressive move against the competition. SPC must also classify its clients and target true friends and butterflies in the introduction of new technologies.
The action plan for SPC's marketing strategy is for the company to build its capabilities and match them with the demands of the customer and the market. Also, high-tech customers must be educated and the product benefits and applications communicated effectively through the utilization of appropriate advertising and promotional mix.
In partial fulfillment of the requirements of TM 299
Thesis
Keywords: Marketing; Measuring instruments